(untitled) (Academia Science Repository, 2023)
Learning to listen will greatly help us improve another desired ability. People expect to hear several varieties of English on a regular basis if they are to communicate effectively, meaningfully, and spontaneously. The purpose of this article is to investigate the significance of listening methods, listening strategies in teaching, and listening processes. Another goal of this article is to demonstrate teachers how they might affect students’ learning processes, namely by adopting tactics to help students learn by listening.